A Critical Analysis of the Infrastructure and Procedural Challenges in E-KTP Services at Kecamatan Sei Beduk, Batam - Melia Sania; Lubna Salsabila; Iranda Firiansyah; Etika Khairina (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
In order to create an orderly society in terms of population administration and ensure the sustainability of national population data, the government is responsible for providing complete and clear population data. It is expected that government officials across Indonesia, particularly in Batam City, deliver high-quality public services in accordance with Standard Operating Procedures (SOPs) and public expectations. However, there are still areas for improvement in public services, especially in Batam. This research aims to critically analyze the quality of e-KTP services at the Sei Beduk sub-district in Batam City, focusing on the infrastructure and procedural challenges that impact service delivery. A qualitative descriptive approach was used in this study. Data was collected, reduced to relevant findings, and presented narratively. The results indicate that the service quality in the Sei Beduk sub-district is generally good, with services facilitating e-KTP issuance. However, the process is often delayed due to issues such as the absence of stamps from the central office. Employee discipline is another challenge, as some staff members still fail to adhere to working hours. Additionally, the sub-district office is equipped with only one recording device, which significantly hampers the efficiency and quality of the service. These infrastructural and procedural challenges must be addressed to improve the overall quality of e-KTP services in the region.